Penerapan Model Pembelajaran Discovery Learning Berbantuan Program Cabri 3D untuk Meningkatkan Hasil Belajar Peserta Didik Materi Pokok Dimensi Tiga - Hutapea, Lisbeth (Desimal: Jurnal Matematika, 2019)
This study aims to improve student learning outcomes in the three dimensional material with the Discovery Learning model assisted by the 3D CABRI program. The type of research used is Classroom Action Research. The results showed that discovery learning learning models assisted by Cabri 3D media can improve student learning outcomes. This is evidenced by an increase from the pre cycle with the class average value of 63.06 increasing to 63.89 in the first cycle and in the second cycle the average increased again to 83.13. Classical learning completeness also increased from 9.26% in the pre-cycle to 38.89% in the first cycle and increased again in the second cycle to 80%.